(untitled) (Journal of Engineering, 2025)
One of the challenges that arises frequently when carrying out residential investment projects is building delays. This study aims to fill this gap and add more to the body of knowledge about residential investment projects in Iraq. The research methodology was divided into two sections: one on previous studies, as mentioned in this research, and the other on techniques and tools for reducing residential project delays. The researcher concluded that there are several issues with residential projects, like inadequate project comprehension, outdated methods, untrained contractors, etc. This issue is not readily resolved and can have a detrimental effect on the project’s outcome, including cost overruns, subpar work, a lack of safety, and schedule delays. In addition to other detrimental social effects, project delays may occur at some point during the construction process, and in certain cases, even when the project is completed. A construction project must be completed on schedule and within the projected budget. Approximately eighty-four pertinent articles over the past twenty-five years have been examined. This issue has a direct influence on people’s lives and social welfare. Implementing residential project policies for new clients has sparked building projects and increased demand for residential buildings. However, a lot of residential projects were abandoned or never finished, which seriously concerned the government.